Comparative Effectiveness of Combined and Single Neurostimulation and Traditional Dysphagia Therapies for Post-Stroke Dysphagia: A Network Meta-Analysis. (April 2023) - Banda, Kondwani Joseph; Wu, Ko-Chiu; Jen, Hsiu-Ju; Chu, Hsin; Pien, Li-Chung; Chen, Ruey; Lee, Tso-Ying; Lin, Sheng-Kai; Hung, Shih-Han; Chou, Kuei-Ru
Background: Comparative therapeutic benefits of combined and single neurostimulation therapies including neuromuscular electrical stimulation (NMES), pharyngeal electrical stimulation (PES), repetitive transcranial magnetic stimulation (rTMS), transcranial direct current stimulation (tDCS), and traditional dysphagia therapy (TDT) remain unknown in post-stroke dysphagia (PSD) rehabilitation. Therefore, we performed the first network meta-analysis (NMA) to determine comparative effectiveness of combined and single neurostimulation and traditional dysphagia therapies for PSD. Methods: A frequentist NMA model was performed with therapy effect sizes presented as standardized mean differences (SMD) and corresponding 95% confidence interval (95% CI) for therapy comparisons while netrank function ranked the therapies in R-Software. Meta-regression models for study characteristics were analyzed using Bayesian NMA Model. Results: Overall, 50 randomized controlled studies with 2250 participants were included. NMES + TDT 3.82 (95% CI, 1.62-6.01), tDCS + TDT 3.34 (95% CI, 1.09-5.59), rTMS + TDT 3.32 (95% CI, 1.18-5.47), NMES 2.69 (95% CI, 0.44-4.93), and TDT 2.27 (95% CI, 0.12-4.41) demonstrated very large effect in improving swallowing function. NMES + TDT −0.50 (95% CI, −0.68 to −0.32, rTMS + TDT −0.44 (95% CI, −0.67 to −0.21), TDT −0.28 (95% CI, −0.46 to −0.10), and NMES −0.19 (95% CI, −0.34 to −0.04) demonstrated medium to small effect in reducing pharyngeal transit time (PTT). rTMS −0.51 (95% CI, −0.93 to −0.08) demonstrated medium effect in reducing oral transit time (OTT). No significant therapy comparison differences were found for reducing aspiration/penetration. The highest ranked therapy was NMES + TDT for better swallowing function and reduction of PTT, rTMS for reduction of OTT, and tDCS + TDT for reduction of aspiration/penetration. Therapeutic effects of the therapies were moderated by frequency, sessions, and duration. Conclusion: Combined therapies including NMES + TDT, tDCS + TDT, and rTMS + TDT demonstrate better therapeutic effect for improved swallowing function and reduction of PTT, OTT, and aspiration/penetration for PSD.